Entrepreneurial Intention in Vocational Education: Learning, Literacy, and Family Support - Sulastri Rini Rindrayani; Trya Meyla Nur Azizah; Kadeni Kadeni (IJE : Interdisciplinary Journal of Education, 2026)
Entrepreneurial intention is a proximal antecedent of venture creation and is particularly consequential in vocational education, where graduates are expected to contribute as both skilled employees and prospective job creators. This study examined whether entrepreneurship education, entrepreneurial literacy, and the family environment predicted the entrepreneurial intentions of vocational high school students. A quantitative, cross-sectional explanatory design was adopted. The population comprised 716 Grade XI students at SMK Negeri 2 Tulungagung, Indonesia, and 257 respondents were selected through proportionate stratified random sampling. Data were collected using a five-point Likert-scale questionnaire and analyzed by multiple linear regression in SPSS 27. The instruments demonstrated strong internal consistency, and the regression assumptions of normality, linearity, absence of problematic multicollinearity, and homoscedasticity were satisfied. Entrepreneurship education (β = .414, p < .001), entrepreneurial literacy (β = .302, p < .001), and the family environment (β = .159, p = .010) each significantly and positively predicted entrepreneurial intention. Collectively, the predictors explained 66.0% of the variance in entrepreneurial intention (adjusted R² = .660), and the overall model was significant, F (3, 253) = 166.646, p < .001. These findings complement the Theory of Planned Behavior by showing that educational experience, knowledge-based capability, and family support constitute mutually reinforcing contextual conditions associated with students’ entrepreneurial career intentions. Vocational schools should therefore combine experiential entrepreneurship education, systematic entrepreneurial-literacy development, and structured family engagement to strengthen students’ readiness for venture creation.